Cutting Torque and Blowing Effect of Slanted Blade Model for Rotary-Type Mower - I Nengah Suastawa; Radite Praeko Agus Setiawan; Prima Sanjaya (Jurnal Keteknikan Pertanian, 2003)
Rotary-type mower is commonly used for cutting turfgrass as a part of landscape maintenance. Cutting torque and quality to turf surface resulted by cutting are two important factors that have to be considered in designing rotary-type mower blades. The objectives of this research are to design and build a slanted blade model, and to study its cutting torque, blowing effect, and friction between blades and turf surface on a several rotational speeds, slant angles and blade types. The blade model was tested on a specially designed turf-bin test apparatus.